Relevans, legitimitet og resultatkrav – eit komparativt blikk på utfordringane for dei store nasjonale ordboksverka i Norden i dag - Bakken, Kristin (Nordiske Studier i Leksikografi, 2006)
Relevance, Legitimacy and Demands of Completion – a comparison of the ways the national dictionaries in Scandinavia are challenged today. Five of the national dictionaries in Denmark, Sweden and Norway are presented in order to compare them with regard to the challenges they meet in contemporary society. Several of them were conceptualised several decades or even more than a century ago, meaning that they were motivated both by different cultural contexts and by different scientific ideals. At the same time these projects are extremely costly, thus demanding public funding. The paper focuses on four challenges pertaining to this situation: the challenge of securing the financial foundations, the challenge of giving the projects legitimate motivation, the challenge of enhancing their social and scientific relevance, and the challenge of dealing with demands of completion.